2008
DOI: 10.1080/09297040701594888
|View full text |Cite
|
Sign up to set email alerts
|

Memory and Response Inhibition in Young Children with Single-Suture Craniosynostosis

Abstract: Using two versions of the A-not-B task, memory and response inhibition were assessed in 17-to 24-month-old children with surgically corrected single-suture craniosynostosis (cases) and unaffected children (controls). Children's development and language were initially assessed on average at 6-7 months of age and again at this second visit. Cases and controls performed at equivalent levels on average, with cases performing slightly better than controls on several of the variables measured. However, fewer cases t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 67 publications
0
8
0
2
Order By: Relevance
“…Young children with nonsyndromic craniosynostosis obtained memory and response inhibition task scores that did not deviate significantly from the scores of a control group without craniosynostosis. 394 …”
Section: Nonsyndromic Craniosynostosismentioning
confidence: 99%
“…Young children with nonsyndromic craniosynostosis obtained memory and response inhibition task scores that did not deviate significantly from the scores of a control group without craniosynostosis. 394 …”
Section: Nonsyndromic Craniosynostosismentioning
confidence: 99%
“…With respect to the contribution of timing of surgical intervention and developmental outcome, most studies addressing this issue have failed to find an association between age at surgery and postoperative developmental status [11,14,[20][21][22]. However, Arnaud et al, [23] and Bottero et al, [24] found that post-operative mental outcome was better when surgery was performed before one year of age.…”
Section: Timing Of Surgical Intervention Severity Of Synostosis and mentioning
confidence: 99%
“…Further, there was a ‘downward shift’ in the distribution of scores among cases relative to test norms, with cases more likely than controls to score below average relative to test norms and less likely to score in the above average or superior range. In addition to these broad measures, at age 18 months we completed experimental tasks based on the A not B paradigm (Toth et al, 2008) to assess early executive function (EF) and inhibition. Group differences on these tasks were negligible, though fewer children with SSC than controls were able to complete the most challenging tasks, possibly indicating problems with EF under more demanding conditions.…”
mentioning
confidence: 99%